2007
DOI: 10.1108/01409170810845930
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating government website accessibility

Abstract: PurposeThis study seeks to provide insightful information about web accessibility based on human judgment in one Asian country (i.e. South Korea) in comparison to the USA.Design/methodology/approachThis study applies both the automated software tool and the human review of web content to measure website accessibility.FindingsOverall accessibility errors found from the Korean government websites are approximately two times higher than those from the US government websites. The accessibility errors are found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Brajnik et al [22] demonstrated the ability of expert users to detect accessibility violations with more reliability. However, Hong et al [23] conducted a study to compare web accessibility evaluation using human experts and automated software separately. The outcomes of their study showed that automated software tools have the ability to discover more accessibility errors than human experts.…”
Section: Web Accessibility Evaluation Approachesmentioning
confidence: 99%
“…Brajnik et al [22] demonstrated the ability of expert users to detect accessibility violations with more reliability. However, Hong et al [23] conducted a study to compare web accessibility evaluation using human experts and automated software separately. The outcomes of their study showed that automated software tools have the ability to discover more accessibility errors than human experts.…”
Section: Web Accessibility Evaluation Approachesmentioning
confidence: 99%
“…Hackett et al studied the accessibility of higher education websites to study the effect of technological advances and found that Higher education web sites become progressively inaccessible as complexity increases [26]. Kane et al analyzed the websites of top university websites and found that a large number of websites still have accessibility problems [28]. Hong et al examined the accessibility of Korean and U.S. government websites using the automated tools and then compared the results obtained by automated tools with that of human evaluation [28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Few institutions included accessibility features, which required manual verification. Hong et al (2008) in the paper on evaluating government web site accessibility entitled "Software tool vs human experts" provide insightful information about web accessibility based on human judgment in one Asian country (South Korea) in comparison to the USA. This study applies both the automated software tool and the human review of web content to measure web site accessibility.…”
Section: Literature Reviewmentioning
confidence: 99%